HYPOTHYROIDISM OCCURS DUE TO IODINE DEFICIENCY, THE HORMONAL ASSAY T3, T4 AND TSH DONE BY ELISA TEST IN UJJAIN DISTRICT MP INDIA - JaishreeJatwa (International Journal of Research -GRANTHAALAYAH, 2015)
Hypothyroidism is a ‘Public health problem occurs due to Iodine deficiency and it is mostly described in Human population; significantly it is more common in female, than males. Interpretation of the TSH level depends upon the level of thyroid hormone; T3, T4 and TSH, low value of T3, T4 and high value of TSH defines thyroid disorders; Hypothyroidism and its vice-versa condition is Hyperthyroidism, the hormonal assay done by ELISA (Enzyme Link Immunosorbent Assay) test.